A relação entre produção científica e avaliação da Capes : um estudo cientométrico através da ferramenta ScriptSucupira - Fagá, Isadora Trombeta (2016)
The universities have, over the years, consolidating its role as a locus of production and development of scientific and technological research. Therefore, it is essential to analyze the scientific production generated, as well as the creation of evaluations of graduate programs. In Brazil, Capes has the role to coordinate the national system policy graduate and realize, through the report Coleta/Capes and Sucupira Platform, the assessment of master’s and doctoral programs. To facilitate this assessment, the information contained in the reports should be arranged in five categories with different values to each other. One such category entitled Intellectual Production comprises publications in journals, item that has a significant value on the final note of a graduate program. Since currently there is information transparency of graduate programs derived from Sucupira Platform and from Lattes Platform, it emerges as a research question if it is possible a tool that enables the generation and analysis of production indicators of Brazilian Postgraduate programs. Thus, the aim of this study is to analyze, through the Lattes Curriculum, periodicals of two graduate programs: the Graduate Program in Materials Science and Engineering (PPGCEM) and the Graduate Program in Science, Technology and Society (PPGCTS), both from the Federal University of São Carlos. To accomplish this, it was analyzed two periods of evaluation of Capes: the previous three years (2010-2012) and the current period (2013 – April 2015). The data extraction procedures used is ScriptSucupira software and the analysis procedure is Case Study. It was also used collaborative networks with both programs analyzed using the Gephi software. As a result of this research, there was the importance of updating the Lattes curriculum, and the fact that time and area of programs can have a significant weight in the notice that a program receives. In addition, the integration between the teachers and students of a program should be encouraged as a way to improve the bibliographic production and hence the evaluation. It follows, too, that ScriptSucupira tool is effective because it allows a large mass of information to be analyzed.